2013
DOI: 10.1039/c3cc38764j
|View full text |Cite
|
Sign up to set email alerts
|

Pd(ii)-catalyzed decarboxylative acylation of phenylacetamides with α-oxocarboxylic acids via C–H bond activation

Abstract: A palladium-catalyzed decarboxylative acylation of phenylacetamides with α-oxocarboxylic acids via C-H bond activation is described. This protocol provides efficient access to a range of ortho-acyl phenylacetamides, which can be easily converted to 3-isochromanone derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…[1][2][3][4][5][6] During the past few years, significant advances have been made in the formation of C-C bonds via the direct functionalization of C-H bonds catalyzed by palladium. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The transition-metal-catalyzed direct aroylation of arenes bearing different directing groups (such as arylpyridines, benzamides, 2 acetophenone oximes and anilides) C-H bond represents a direct and promising approach to access ketones. [21][22][23][24][25][26][27][28][29][30][31] Many successful strategies involve Pd-catalyzed ortho-coupling reactions with C-H bonds through cyclopalladation of 2-phenylpyridine.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] During the past few years, significant advances have been made in the formation of C-C bonds via the direct functionalization of C-H bonds catalyzed by palladium. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] The transition-metal-catalyzed direct aroylation of arenes bearing different directing groups (such as arylpyridines, benzamides, 2 acetophenone oximes and anilides) C-H bond represents a direct and promising approach to access ketones. [21][22][23][24][25][26][27][28][29][30][31] Many successful strategies involve Pd-catalyzed ortho-coupling reactions with C-H bonds through cyclopalladation of 2-phenylpyridine.…”
Section: Introductionmentioning
confidence: 99%
“…Phenylacetic scaffold is featured in pharmaceuticals and other bioactive compounds . For its functionalization, numerous C–H activation‐based methods have been developed including arylation, alkenylation, alkylation, alkynylation, halogenation,[6b], [6f], acylation, deuteration, lactonization and acetoxylation. [6b], [7f], [13b], Generally, the acetoxylation of arylacetic acids cannot be performed without installation of an amide directing group (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…2 Later Ge et al reported the Pd-catalysed decarboxylative acylation of acetanilides and 2-aryl pyridines at the orthoposition of the phenyl ring with α-oxocarboxylic acids via ligand-assisted ortho-C(sp2)-H activation in the presence of an oxidant. 3 Subsequently different directing groups including azobenzenes, 4 azoxybenzenes, 5 carboxylic acids, 6 cyclic enamides, 7 O-methyl ketoximes, 8 O-phenyl carbamates, 9 phenylacetamides, 10 2-aryloxypyridines, 11 pyridine-N-oxides, 12 indolines, 13 thioethers, 14 N-nitroso anilines, 15 tetrahydroquinolines 16 and indoles 17 have been used for performing the acylation via ligand-assisted activation of the ortho-C(sp2)-H bond leading to formation of biaryl ketones with high regioselectivities under mild reaction conditions. β-Carboline, a privileged scaffold, is core unit of several natural alkaloids and bioactive compounds endowed with diverse pharmacological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Hz, 1H),10.07 (d, J = 8.5 Hz, 1H), 11.11 (s, 1H) 13. C NMR (100 MHz, CDCl 3 ): δ (ppm) = 112.2, 116.0, 120.3, 121.5, 121.7, 126.2, 126.6, 128.9, 129.1, 129.2, 131.0, 131.6, 132.3, 132.8, 134.9, 136.0, 136.2, 137.9, 138.5, 140.9, 155.7, 158.6.…”
mentioning
confidence: 99%